2010
DOI: 10.1007/s10792-010-9344-5
|View full text |Cite
|
Sign up to set email alerts
|

Light sensitivity and pain sensation during cataract surgery. A comparative study of two modes of anaesthesia

Abstract: The objective of this study was to compare the light sensitivity and pain experienced by patients undergoing cataract surgery under subtenon and topical with intracameral anaesthesia. Fifty-four patients were randomly assigned to receive either two drops of proxymethacaine 0.5% as topical anaesthesia with 0.5 ml preservative-free 1% intracameral lidocaine or 4 ml 2% lignocaine as subtenon anaesthesia. Light sensitivity and overall pain perception were recorded at the end of surgery. The mean pain score in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Some studies have also reported that patients can see instruments and movement within their visual field during surgery, and in some cases, where vision is lost completely during surgery, light sensitivity was still present for each patient [ 22 24 ]. High light sensitivity accompanying photophobia symptoms following cataract surgery can result in increased psychological distress for some patients [ 17 ]. This could in turn influence their intraoperative pain perception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have also reported that patients can see instruments and movement within their visual field during surgery, and in some cases, where vision is lost completely during surgery, light sensitivity was still present for each patient [ 22 24 ]. High light sensitivity accompanying photophobia symptoms following cataract surgery can result in increased psychological distress for some patients [ 17 ]. This could in turn influence their intraoperative pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…However, our analysis found that the differences in light sensitivity score between the two surgeries were not statistically significant. Different methods of anesthesia can affect the severity of light sensitivity [ 17 ], and the conditions for use of topical anesthesia for the patients included in our study were identical. We suggest that this is why the light sensitivity scores for the two operations were not significantly different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, patients experience greater discomfort during surgery. 13,14 It can also potentially have an impact on the incidence of intraoperative adverse events in noncompliant patients. 13,14 In private cataract surgery or refractive lens exchange, great emphasis is placed on patient's journey, experience and comfort.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 It can also potentially have an impact on the incidence of intraoperative adverse events in noncompliant patients. 13,14 In private cataract surgery or refractive lens exchange, great emphasis is placed on patient's journey, experience and comfort. Additionally, many surgeons in our practice indicated that the surgery is technically easier if akinesia is achieved with local anesthesia, which is the reason why sub-Tenon's anesthesia with mild sedation is the main technique in our clinical practice.…”
Section: Discussionmentioning
confidence: 99%